Diseño de un sistema integrado de gestión basado en las normas NTC: ISO 9001:2015, 14001:2015 Y 45001:2018 para una empresa de construcción,interventoría y consultoría de obras civiles. (2019)
The company Jorge Eduardo Higuera Higuera JEHH dedicates to the construction and supervision of civil works in the department of Boyacá, it has a problem that revolves around its sales, since approximately 5 years ago has not seen an important growth, the company has not been able to expand their services throughout the territory, it has not achieved solid communication with their clients, on different occasions there have been incidents and accidents at work, and the organization does not have a constant review and update of the legal requirements that correspond to it. Therefore, there is a need on the part of Management to design an effective Integrated Management System based on the NTC ISO 9001: 2015 (Quality Management System); 14001: 2015 (Environmental Management System); and 45001: 2018 (Occupational Health and Safety Management System) based on the PHVA cycle (plan, do, verify, act) that helps to identify hazards and mitigate risks, it be able to have a process-based approach, obtain opportunities to improvement for the organization, among other relevant aspects.